Participatory-prospective construction of extension and research lines of the Chorotega Regional Headquarters of the National University, Costa Rica - Bautista Solís, Pável (2025)
The strategic planning of the universities’ substantive action requires greater comprehensiveness and recognition of extension. In Costa Rica, strategic planning at the local level omits the contextualization with the characteristics of the territory and society. The objective of this work was to document and critically analyze a process of collaborative construction of extension and research lines of the Chorotega Regional Headquarters (SRCH) of the National University (UNA), as an input for institutional and territorial planning. Co-constructing, from a participatory and prospective approach, the academic production of extension, research and lecturing in the period January 2010 - June 2022 was characterized. The process included: bibliometric analysis, text mining and participatory-prospective workshops to identify strategic areas, thematic lines and future scenarios based on the local context and the experience of the SRCH. A total of 442 documents were identified, mainly extension documents that are not usually indexed in research databases. Academic production at SRCH is multi-, inter- and trans-disciplinary, comprising seven strategic areas and 26 lines of extension and research. The process contributes methodologically to the strategic planning of the substantive Ibero-American university action and contributes to the visibility and valorization of the academic production of university extension.